MODELING OF INDIVIDUAL TELERADIOGRAPHIC INDICATORS ACCORDING TO DOWNS METHOD FOR YOUNG MEN AND YOUNG WOMEN WITH DIFFERENT FACE TYPES - Drachevska, I.Yu.; Barylo, О.S.; Shevchuk, Yu.G.; Gunko, I.P.; Kondratiuk, А.І. (World of Medicine and Biology, 2021)
In Ukrainian young men (with a wide face type) and young women (with a wide and very wide face type) with orthognathic occlusion, reliable regression models of individual teleradiographic indicators of the upper and lower jaws were constructed and analyzed by the Downs method (second group) depending on the basic cephalometric parameters (first group) (in young men R²= 0.856 and 0.902, most often the models include the value of the distances N-S and S-E; only in young women with a wide type of face – R²=0.778); and indicators that characterize the position of each tooth (third group), depending on the indicators of the first and second groups (in young men R²= from 0.605 to 0.868, most often the models include the value of the angles NAPog, POr-GnS, AB-NPog and distances N-S and P-PTV; respectively in young women – R²= from 0.614 to 0.801, most often the models include the value of the angle AB-NPog, and R²= 0.718 and 0.860, most often the models include the value of the angles NAPog, POr-MeGo, POr-GnS, Н and distance S-E).
Keywords: teleradiography; Downs method of cephalometry; young men and young women with orthognathic occlusion; facial types; regression analysis